Crisis recovery in a country with a high presence of foreign owned companies: The case of Ireland - Heike Joebges (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2017)
Compared to other euro area countries, Ireland has been one of the countries most heavily hit by the worldwide financial crisis, yet, also one with the strongest and quickest recovery. Foreign controlled affiliates of multinational companies dominate economic activity, attracted by low corporate taxation rates. Low Irish tax rates contribute to downward competition of taxation in the EU and constitute a beggar-thy-neighbour-policy. Effects on Ireland are neither clearly positive: Profits of foreign affiliates do not necessarily stay in the country. A consequence is the huge difference between GNI and GDP: GNI per capita is by about 15 percentage points lower than GDP per capita. Hence, GDP can be misleading, when judging the recovery since the financial crisis. The paper instead concentrates on the development of national income, employment, and wages. Judged by these indicators, the Irish recovery ceases to be successful compared to other crisis countries. The benefits to Irish citizens are nevertheless questionable: GNI decreased stronger than GDP. Even worse are labour market developments since the recent crisis: employment and wages are still to recover, and the wage share decreased by more than 10 %-points. – – Irland hat im Zuge der weltweiten Finanzkrise einen der stärksten Wachstumseinbrüche verzeichnet, sich aber auch schneller als andere Krisenländer davon erholt, wenn man die Wirtschaftsentwicklung mit dem Bruttoinlandsprodukt (BIP) misst. Die Konzentration auf die BIP-Entwicklung ist aber problematisch in einem Land mit hohem Anteil von Unternehmen in ausländischem Besitz, da die Gewinne dieser Unternehmen größtenteils repatriiert werden. Folglich sind die Einkommen der Inländer deutlich geringer als es das BIP suggeriert: Das Bruttonationaleinkommen (BNE) liegt ca. 15 Prozentpunkte unter dem BIP. Um die Krisenfolgen für die Inländer besser zu erfassen, konzentriert sich die Studie auf die Entwicklung von nationalen Einkommen, Löhnen und der Lohnquote. Nach diesen Indikatoren hat sich Irland nicht besser als andere Krisenländer im Euroraum von den Krisenfolgen erholt. Einkommen und Löhne haben die Vorkrisenniveaus noch nicht erreicht, während die Lohnquote um mehr als 10 Prozentpunkte gefallen ist. Dass nicht einmal die Inländer eindeutig von der hohen Präsenz ausländischer Unternehmen profitieren, ist problematisch, weil Irland diese gezielt mit einer niedrigen effektiven Unternehmensbesteuerung anlockt, die negative Auswirkungen auf andere Euroraumländer hat.
urn:nbn:de:101:1-201703015227
Keywords: 330